Wizzmie Customer Purchasing Decision Model in Semarang City: Shopping Experience Involvement as a Mediating Variable (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2025)
This study aims to analyze the factors influencing Wizzmie customer purchasing decision model in Semarang City: shopping experience involvement as a mediating variable. This study is a type of quantitative research with primary data sources in the form of questionnaires. The sampling method in this study uses the Hair formula which obtained 140 research samples. The analyzed data used in this study is the Structural Equation Model (SEM) with Smart PLS 3.0 software. The results of this study state that store atmosphere and shopping experience have a positive and significant effect on purchasing decisions. Conversely, brand image, social media marketing, and service quality do not have a significant direct effect on purchasing decisions. However, shopping experience is proven to be able to mediate the influence of store atmosphere, social media marketing, and service quality on purchasing decisions. Thus, although not all variables have a direct effect on purchasing decisions, some of them can indirectly influence through shopping experience as a mediating variable.